Virulence of entomopathogenic bacteria Serratia marcescens against the red palm weevil, Rhynchophorus ferrugineus (Olivier) - Baozhu Zhong; Chaojun Lv; Wenlian Li; Chaoxu Li; Tuo Chen (PeerJ, 2023)
Background The red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier), is an important quarantine pest, which has caused serious economic losses in various palm species, such as coconut, oil palm and date palm. Finding effective biocontrol resources is important for the control of this pest and the protection of palm crops. Methods A pathogenic strain HJ-01 was isolated from infected and dead pupa of Tenebrio molitor using tissue separation method. The HJ-01 strain was streak cultured and purified, and its morphological, physiological, biochemical characteristics, and 16S rDNA homology were identified after conducting a pathogenicity test on RPW larvae. Results Strain HJ-01 exhibited remarkable pathogenicity against RPW larvae. Under the concentration of HJ-01 suspension was 1.0 × 108 cfu/mL, the mortality rate of RPW reached 82.22%, and the half-lethal time (LT50) was 4.72 days. RPW larvae infected with strain HJ-01 showed reduced movement, decreased appetite, and eventual death. As the treatment progresses, the larvae’s bodies turned red, became soft, and started to rot, resulting in the discharge of liquid. HJ-01 demonstrated the ability to produce scarlet pigment after 24 h of culture on a basic medium. Colonies of HJ-01 appeared convex, bright red, moist, and viscous, opaque in the center, irregular at the edges, and emitted an unpleasant odor. Under microscopic observation, the cells of HJ-01 appeared as short rod-shaped and flagellate, with a size ranging from (1.2–1.8) μm × (1.0–1.2) μm. Genomic DNA extraction was performed on the strain, and the 16S rDNA sequence was amplified, yielding a sequence length of 1445 bp. The sequence of strain HJ-01 displayed a 99.72% similarity to that of Serratia marcescens. Phylogenetic tree analysis further confirmed that strain HJ-01 belonged to S. marcescens. Therefore, the strain HJ-01 has a very good lethal effect on RPW larvae, and it may be used as an effective bacterium for the control of RPW.